51.5k views
4 votes
F(1) = -2
f(2) = 5
(f(n) = f(n − 2). f(n - 1)
f(3) =

1 Answer

0 votes

Answer:

f(3) = -10

Explanation:

The formula given is f(n) = f(n − 2). f(n - 1)

For the first term in the quotient:

if n = 3 then substitute the result of f(3 − 2) = f(1) spot, which is given by the number -2.

for the second term in the quotient:

if n = 3 then substitute the result of f(3 − 1) = f(2) spot, which is given by the number 5.

Now combine this and you get:

f(3) = -2 * 5

f(3) = -10

User Acm
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.